Bioassay of Plant-based and Synthetic Insecticides for the Management of Tomato Leaf Miner, Tuta absoluta (Meyrick) in Open-field Conditions in Salyan, Nepal - Pandey, Nabin; Tiwari, Sundar (Far Western Review, 2024)
The tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), has invaded most parts of Nepal and threatens tomato production. Their management primarily relies on insecticides in Nepal. Market-available and locally-madeplant-based pesticides are not equally effective in managingT. absoluta. Therefore, this study aimed to evaluate the effectiveness of such potential insecticides in managing T. absoluta in open-field conditions. This study was carried out in the Salyan district of Nepal in 2021 and treatments were designed in a randomized complete block design (RCBD)with seven treatments and three replications. All treatments were sprayed at12-dayintervalsfor two times. The treatments used were Emamect in benzoate 5% SC, Imidacloprid 17.8 SL, Jholmol (botanical mixture extract and urine mixture), Chlorantraniliprole 18.5 SC, Spinosad 45 SC, Azadirachtin 300ppm and Control. The results showed that the lowest percentage of leaves and fruit damage was recorded in Chlorantraniliprole 18.5 SC and Spinosad 45 SC sprayed plots. Insecticide efficiency was ranked as Chlorantraniliprole > Spinosad>Ema-mectin Benzoate > Azadirachtin >Imidaclroprid>Jholmol>Control. Marketable yield was obtained highest in Chlorantraniliprole (85.26 t/ha) treated plots followed by Spinosad (79.26 t/ha); both were not significantly different. This study provides an opportunity to select the most suitable and effective pesticides for the management of tomato leaf miners and can be used in integrated pest management strategies as a selective insecticides.